Wing of the word that raises you up. The poetry of César Augusto Ayuso - Martínez, José Enrique (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Afirmación del hombre was the first poetry book by César Augusto Ayuso published in 1980 and the last one Respirar de los días in 2008. In this paper, a poetic trajectory that covers almost thirty years and that was drifting towards expressive containment, brevity, lightness and mood vibration is formally and thematically reviewed.